Electrochemical Analysis of Ascorbic Acid in Commercial Fruit Juices and Drinks - Siriangkhawut, Watsaka (Asian Journal of Chemistry, 2014)
Simple, reliable and inexpensive methods based on oxidation of ascorbic acid, differential pulse polarography and potentiometric titration, were validated for determination of ascorbic acid in commercial fruit juices and fruit drinks consumed in Thailand. For differential pulse polarography, the 0.1 M citrate buffer pH 4.6 was used as supporting electrolyte. The linearity was found in the range of 2.5-100 mg/L ascorbic acid with limit of detection and quantitation at 0.6 and 1.9 mg/L, respectively. The repeatability and reproducibility at 50 mg/L were 0.043 and 0.96 %, respectively. The potentiometric titration was performed using combined Pt-ring electrode with 2,6-dichloroindophenol as titrant. The method showed excellent linearity over the tested concentration ranges (100-350 % of the amount found in the juice samples), good precision (RSD < 2 %) and recovery (> 94 %). The limit of detection and limit of quantitation were 0.05 mg and 0.165 mg, respectively. The quantitation of vitamin C content in commercial fruit juices and drinks determined by both methods were in good agreement at 95 % confidence level with high percentage recoveries in the range of 89-105 %. Found levels of ascorbic acid in most samples by both methods were not in good agreement with those stated on the nutritional label.